A systematic review of the effectiveness of patient-based educational interventions to improve cancer-related pain. (February 2018) - Oldenmenger, Wendy H.; Geerling, Jenske I.; Mostovaya, Irina; Vissers, Kris C.P.; de Graeff, Alexander; Reyners, Anna K.L.; van der Linden, Yvette M.
Highlights: Cancer-related pain is one of the most frequently occurring symptoms. Patient pain education programs improve patients' knowledge about cancer pain. Effect of education programs on pain remains unclear due to the heterogeneity. Future studies should standardize reporting of their interventions. Abstract: Background: Despite existing guidelines to assess and manage pain, the management of cancer-related pain is often suboptimal with patients often being undertreated. Inadequate pain management may be due to patient-related barriers. Educating patients may decrease these barriers. However, the effect of pain education on patient-related outcomes is still unclear. This review aimed to study the effect of educational interventions on cancer-related pain. Design: We performed a systematic review of randomized controlled trials (RCTs) identified from Medline and Cinahl, from 1995 to May 2017. Two reviewers independently selected trials comparing educational intervention to usual care or an active control intervention. The methodological quality was assessed and data extraction was done independently. Primary outcome measures were pain intensity and interference. Secondary outcome measures were knowledge/barriers, medication adherence and self-efficacy. Results: Twenty-six RCTs totaling 4735 patients met our inclusion criteria. Compared to the control group, 31% of the studies (including 19% of all patients) reported a significant difference in pain intensity in favor of the intervention group. Twelve studies measured pain interference and four (30%) found a significant improvement. With regard to secondary endpoints, significant differences in favor of the experimental arms were found for pain knowledge or barriers (15/22 studies; 68%), medication adherence (3/6 studies; 50%) and self-efficacy (1/2 studies). Conclusions: Patient-based pain educational programs may result in improvements of relevant patient-reported outcomes. However, the interventions are heterogeneous and improvement of pain was only seen in less than one third of the studies and in less than 20% of all included patients.